Research of conflicting interests in the field of intellectual property - Kosenko, A. V.; Petrova, M. Ye. (Харківська державна наукова бібліотека імені В. Г. Короленка, 2024)
The report is devoted to the analysis of conflicting interests that arise in the field of intellectual property (IP). The relevance of the topic is due to the rapid development of technologies and innovations, which, in turn, leads to an increase in the number of cases where IP rights may contradict each other. The report examines the main types of conflicts of interest that may arise between different participants in legal relations, such as authors, investors and companies, as well as their impact on the protection of intellectual property rights. The practical significance of conflicts of interest and their consequences for business are analyzed, in particular in the context of legal disputes and ethical aspects.

Доповідь присвячена аналізу конфліктних інтересів, що виникають у сфері інтелектуальної власності. Актуальність теми зумовлена стрімким розвитком технологій та інновацій, що, в свою чергу, веде до підвищення числа випадків, коли права на ІВ можуть суперечити одне одному. У доповіді розглядаються основні види конфліктів інтересів, які можуть виникати між різними учасниками правовідносин, такими як автори, інвестори та компанії, а також їх вплив на захист прав інтелектуальної власності. Аналізується практична значущість конфліктів інтересів та їх наслідки для бізнесу, зокрема у контексті юридичних спорів та етичних аспектів.
Дослідження конфлікту інтересів у сфері інтелектуальної власності
Keywords: intellectual property; legal support; conflict situations; legal protection; інтелектуальна власність; правове забезпечення; конфліктні ситуації; правовий захист